JALTCALL Pubs 2021
DOI: 10.37546/jaltsig.call2020.1
|View full text |Cite
|
Sign up to set email alerts
|

The NGSL Project: Building Wordlists and Resources to help EFL Learners (and Teachers) to Succeed

Abstract: During my JALTCALL 2020 Plenary Address, I explained about the importance of high frequency and special purpose (SP) vocabulary for second language learners of English, and then went on to introduce our New General Service List Project, a collection of 7 open-source, corpus-based word lists offering the highest coverage in each of their specific genres, as well as the large and growing number of free apps and online tools we have either developed or utilized to help learners, teachers, researchers and material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Learning those words will be undoubtedly necessary because when they enter a university or college, they will need to be familiar with academic words or technical words in their majors. However, it would take many years for Japanese learners to master high-frequency words (Browne, 2021), asking them to learn mid-or lowfrequency words including specialized vocabulary words is impractical. According to Nation (2013), those words can be effectively learned by paying special attention to them.…”
Section: Discussionmentioning
confidence: 99%
“…Learning those words will be undoubtedly necessary because when they enter a university or college, they will need to be familiar with academic words or technical words in their majors. However, it would take many years for Japanese learners to master high-frequency words (Browne, 2021), asking them to learn mid-or lowfrequency words including specialized vocabulary words is impractical. According to Nation (2013), those words can be effectively learned by paying special attention to them.…”
Section: Discussionmentioning
confidence: 99%
“…The list of non-academic words was referred to the New General Service List (NGSL) developed by Browne, Culligan, and Phillips (2013). The NGSL is the updated version of the original General Service List developed by Michael West initially in 1936 and its last version in 1953, considering the fast development and dynamic changes of English words (Browne 2021). This list includes core high-frequency vocabulary words for students of English as a second/foreign language.…”
Section: Methodsmentioning
confidence: 99%
“…However, it is also suggested that the students do not exclusively learn the academic words but also need to learn general words that might be useful to discuss specialized academic discourses. Academic and general words are necessary for students to survive during their study, since they can be a shortcut for students to learn the essential words in their learning context (Browne 2021).…”
Section: Pedagogical Implicationsmentioning
confidence: 99%
“…In light of these considerations, a major pedagogical challenge in teaching English to speakers of other languages (TESOL) has been addressing the vocabulary learning needs of learners at different stages of language learning (Nation, 2013). Over the past decades, this consistent concern resulted in the creation of a number of corpus-based word lists for high-frequency and academic vocabulary to inform language teaching materials developments (Coxhead, 2000;Gardner and Davies, 2014;Brezina and Gablasova, 2015;Browne, 2021;Cobb and Laufer, 2021). High-frequency or general service words are commonly used vocabulary items in spoken and written language that provide from 80 to 90% coverage in most texts in English.…”
Section: Introductionmentioning
confidence: 99%
“…The present study aimed to facilitate the learning of highfrequency vocabulary by English as Foreign Language (EFL) learners via mobile devices and DFs. To this end, the highfrequency vocabulary in English is operationalized based on New General Service List (NGSL) project (Browne, 2021) which is among the most recently developed corpus-based core vocabulary lists. The NGSL contains 2,818 items (i.e., flemmas) derived from a 273 million-word subsection of Cambridge English Corpus.…”
Section: Introductionmentioning
confidence: 99%